Application of Kahoot media in learning Mandarin for Z generation learners at Private High School - Azizah, Mirah (Indonesian Journal of Learning Education and Counseling, 2024)
Foreign language education, especially Mandarin, currently requires the involvement of technology both directly and indirectly, this is due to the rapid development of technology. In line with this, Daryanto (2016) put forward the environmental concept including learning places, media methods, assessment systems, as well as the facilities and infrastructure needed to package learning and organize study guidance so as to facilitate student learning. Therefore, innovative and creative media is needed that can add direct experience to students - and be a supporter in evaluation activities so that teachers can find the best way so that students are not left behind, especially in technological developments in learning activities, students can make more use of their devices. Good. One way is to design learning activities, both in the learning process and the evaluation process, using devices owned by students. In this era of rapid development of science and technology, professional teachers are not enough just to have the ability to teach students, but also have to manage information and the environment to facilitate student learning activities. One online media that can be used is Kahoot. Kahoot media is a web tool for creating interesting quizzes, discussions and surveys. Kahoot is also an online application that can be used to create interactive and fun online quiz-based learning evaluation media. The research method used by the author in this research is a qualitative descriptive method, namely by field observation and using interviews and documentation as part of the research collection technique. With the research location at Golden Gate senior high school. The data collection instruments or tools used by the author in this research were journals and other document archives as well as interviewing informants or sources, including the Mandarin teacher at Golden Gate Senior High School.